The Smart Internet Current Research and Future Applications - Chignell, Mark.; Cordy, James; Ng, Joanna; Yesha, Yelena; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The Smart Internet initiative has been spearheaded by IBM and aims to extend and transform the Web so that it is centered on the user, with the web as a "calm" platform ubiquitously providing cognitive support to its users and their tasks. The initiative is attended by two specific areas of research: Smart Interactions, which deal with factors that affect the discovery, aggregation and delivery of resources and content from the internet that concentrates on users and their tasks; and Smart Services, which addresses the enabling infrastructure to support smart interactions - their requirements, functions and relationships. This state-of-the-art survey is based on an NSERC Strategic Workshop on the Smart Internet (SITCON 2009), held in Markham, Canada as part of CASCON 2009 in November 2009. The chapters in this book underwent two rounds of reviewing, selection, and improvement to find their place in this volume, resulting in significant revisions and extensions based on the experts' advice. This volume represents a snapshot of current research and conceptualization of the Smart Internet; after some initial motivating chapters, it is concerned with two major research areas for enabling the Smart Internet, namely, Smart Interactions and Smart Services.
Motivation -- Motivation -- Smarter Healthcare: An Emergency Physician View of the Problem -- The Smart Internet as a Catalyst for Health Care Reform -- Overview of the Smart Internet -- Smart Interactions -- Smart Interactions -- Designing Effective Notifications for Collaborative Development Environments -- Smart Group Interactions -- Supporting Smart Interactions with Predictive Analytics -- A Framework for Automatically Supporting End-Users in Service Composition -- A Survey of Mashup Development Environments -- Smart Media: Bridging Interactions and Services for the Smart Internet -- Smart Services -- Smart Services -- Smart Services Across the Real and Virtual Worlds -- Event Exposure for Web Services: A Grey-Box Approach to Compose and Evolve Web Services -- Towards Web Services Tagging by Similarity Detection -- User-Centric Smart Services in the Cloud -- Monitoring and Recovery of Web Service Applications -- Managing Dynamic Context to Optimize Smart Interactions and Services.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Information Systems Applications (incl.Internet).; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; User Interfaces and Human Computer Interaction; Software Engineering